Efficacy of multimodal, systematic non-surgical treatment of knee osteoarthritis for patients not eligible for a total knee replacement: a study protocol of a randomised controlled trial. Issue 6 (14th November 2012) - Skou, Soren Thorgaard; Roos, Ewa M; Laursen, Mogens Berg; Rathleff, Michael Skovdal; Arendt-Nielsen, Lars; Simonsen, Ole; Rasmussen, Sten
Abstract : Introduction: It is recommended that non-operative treatment of knee osteoarthritis (KOA) should be individually tailored and include multiple treatment modalities. Despite these recommendations, no one has yet investigated the efficacy of combining several non-surgical treatment modalities in a randomised controlled study. The purpose of this randomised controlled study is to examine if an optimised, combined non-surgical treatment programme results in greater improvements in pain, function and quality of life in comparison with usual care in patients with KOA who are not eligible for total knee arthroplasty (TKA). Methods and analysis: This study will include 100 consecutive patients from the North Denmark Region not eligible for TKA with radiographic KOA (K-L grade ≥1) and mean pain during the previous week of ≤60 mm (0–100). The participants will be randomised to receive either a 12-week non-surgical treatment programme consisting of patient education, exercise, diet, insoles, paracetamol and/or NSAIDs or usual care (two information leaflets containing information on KOA and advice regarding the above non-surgical treatment). The primary outcome will be the change from baseline to 12 months on the self-report questionnaire Knee Injury and Osteoarthritis Outcome Score (KOOS)4 defined as the average score for the subscale scores for pain, symptoms, activities of daily living and quality of life. Secondary outcomes include the five individual KOOS subscale scores, pain on a 100 mm Visual Analogue Scale, EQ-5D, self-efficacy, pain pressure thresholds, postural control and isometric knee flexion and knee extension strength. Ethics and dissemination: This study was approved by the local Ethics Committee of The North Denmark Region (N-20110085) and the protocol conforms to the principles of the Declaration of Helsinki. Data collection will be completed by April 2014. Publications will be ready for submission in the summer of 2014. Trial registration number: This study is registered with http://clinicaltrials.gov (NCT01535001 ).